Masculinity and Men's Suicide Attempts in Bangladesh. Issue 4 (19th May 2022) - Khan, Anisur Rahman; Dery, Isaac; Helman, Rebecca
Abstract: Drawing on Raewyn Connell's theoretical notion of hegemonic masculinity, this study examines relations between masculinity and suicide attempts in Bangladesh. In-depth interviews were conducted with 17 men from the Jhenaidah district, who had previously attempted suicide. Participants discussed how "real men" were expected to be primary providers, demonstrate their material power and sexual prowess. However, the men disclosed that they encountered difficulties in achieving these versions of hegemonic masculinity in their real lives. Within this context, suicide attempts operated as a redemptive means to overcome perceived masculine "crises." These findings demonstrate that suicide is a socially and culturally constituted phenomenon, which should be understood beyond an individualized and mental health framework. Suicide intervention strategies in Bangladesh must include critical analyses of masculinities, as well as measures to change rigid processes of gendered socialization.